2012
DOI: 10.2147/ijn.s33014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the intestinal absorption mechanism of icariin in the nanocavities of cyclodextrins

Abstract: Icariin is a bioactive herbal ingredient isolated from Herba epimedii, which has been widely used for the treatment of osteoporosis and male sexual dysfunction in traditional Chinese medicine. The major objective of this work is to investigate the different enhancing effects of β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD) on the intestinal absorption of icariin, and to identify the molecular mechanisms of this action. Host-guest-type interactions of icariin with cyclodextrins nanocavities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Despite the numerous studies on icariin, the main challenge remains its very low oral bioavailability due to the physicochemical characteristics ( Chen et al, 2008 ), and P-glycoprotein-mediated efflux in intestinal mucosa ( Zhang Y. et al, 2012 ). Different studies indicated the importance of icariin hydrolysis by lactase phlorizin hydrolase in the small intestine and by microbiota β-glucosidase to release metabolites before its absorption ( Zhao et al, 2010 ; Chen et al, 2011 ; Qian et al, 2012 ).…”
Section: Pharmacokinetics Of Icariinmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous studies on icariin, the main challenge remains its very low oral bioavailability due to the physicochemical characteristics ( Chen et al, 2008 ), and P-glycoprotein-mediated efflux in intestinal mucosa ( Zhang Y. et al, 2012 ). Different studies indicated the importance of icariin hydrolysis by lactase phlorizin hydrolase in the small intestine and by microbiota β-glucosidase to release metabolites before its absorption ( Zhao et al, 2010 ; Chen et al, 2011 ; Qian et al, 2012 ).…”
Section: Pharmacokinetics Of Icariinmentioning
confidence: 99%
“…Fortunately, the modern techniques offer a range of methods to overcome this issue. To increase icariin bioavailability, researchers have developed several drug delivery systems such as combining icariin with snailase (an exogenous hydrolase) to improve intestinal hydrolysis ( Liu et al, 2017 ), encapsulating icariin into liposome ( Yang et al, 2012 ), producing icariin/hydroxylpropyl-beta-cyclodextrin inclusion complex that enhances intestinal absorption probably through a solubilizing effect and/or the inhibition of P-glycoprotein ( Zhang Y. et al, 2012 ).…”
Section: Pharmacokinetics Of Icariinmentioning
confidence: 99%
“…In the FTIR spectrogram, the characteristic peaks at ≈1650, 1600, 1510, 1070, and 1260 cm −1 can be assigned to free icariin. In differential scanning calorimetry, the endothermic peak at ≈250 °C is related to icariin [ 97 ].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Icariin has a low bioavailability due to its poor absorption, which poses additional limitations to its clinical application ( Li et al, 2015 ). However, it has been found that the bioavailability of icariin can be improved by pharmacological methods ( Zhang et al, 2012 ). Therefore, the studies on the activation of autophagy to maintain the homeostasis of chondrocytes by icariin are of guidance for the prevention and treatment of OA.…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%